"Just Access"? Questions of Equity in Access and Funding for Assistive Technology. Issue 3 (3rd April 2019) - Durocher, Evelyne; Wang, Rosalie H.; Bickenbach, Jerome; Schreiber, Daphne; Wilson, Michael G.
Abstract : Assistive technology has great potential to contribute to health, functioning, and quality of life. To date, as exemplified in the Canadian context, variations and inequities in access to assistive technology are evident; the development of legislation, policies, and programs has not kept up with the increasing use of assistive technology. In this article, we apply ;Daniels's (2008) theory of just health to argue that equitable access to assistive technology funding and services is necessary for justice. In doing so, we offer theoretical guidance for the development of legislation, policies, and programs to guide such access in health and social services.